Transplantation et hybridation transculturelle dans la poésie d’Olive Senior - Myriam Moïse (Éditions en environnement VertigO, 2012)
A metaphor of the Caribbean biodiversity, Olive Senior’s poetry is a Creole meditation on Caribbean landscape and its processes of hybridization, proliferation and reproduction. Senior’s poetic language not only personifies the Caribbean flora but also feminizes it underlining its cross-fertilization as a mean to resist men’s exploitation and to counter the reconquest of the postcolonial space. As a matter of fact, the natural environment depicted by Senior is a fragmented Caribbean landscape, one that is deflowered by colonisation and tourism. Plants are ambivalent symbols embodying both fertility and sterility. The planted seed becomes an allegory of spatial invasion and of remapping, while its hybrid crop resists and comes to feed the memory of the Caribbean people. This poetry of ambivalence is at the heart of the Caribbean diasporic imagination and contributes to the construction of new transcultural identities that proliferate in diasporic spaces.